Análise do efeito valor no mercado acionário latinoamericano: um estudo do desempenho das carteiras Value e Growth no período de 2003 a 2008 - Saad, Roberta Marin Faneco (2009)
The purpose of this dissertation is to investigate the existence of the value effect anomaly on Latin America stock market. The value effect is characterized by high performance of value portfolios (the latter containing with high yields stocks book-to-market, earnings to price and cashflow to price) than growth portfolios (the ones containing with low yields stocks for the same variables). The database is composed by common stocks listed at the main Stock Exchanges of five countries: Argentina, Brazil, Chile, Mexico and Peru, from 2003 to 2008. This data was extracted from Bloomberg database. The employed test methodology was similar to the one developed and used by Fama e French (1998). The monthly return excess of the value and growth portfolios was calculated and compared by country and by Latin American market. Then ran up models of simple and multiple linear regressions in the search for explanation of changes in the returns of portfolios. The Latin American portfolios were formed of two ways: a) weighted average by the amounts negotiated in the stock exchanges of each countries of the monthly excess return of the portfolios by country; b) simple average of the monthly excess return of the portfolios by country. It was used statistical tests such as: t-Student for the comparison of the average return of the value and growth portfolios and the significance of the regression coefficients; Durbin-Watson test of autocorrelation of waste; and Kolmogorov-Smirnov test to verify normality of the series of data. The results indicated that, despite that the value portfolio presented returns higher than the growth portfolios and the market, it is not possible to prove the existence of the value effect over the Latin America market due to low statistics significance of test t. Besides, the CAPM model proved to be significative and superior to the APT two factors model in the explanation of the returns of the value and growth portfolios